Tracking Control of Quadrotors with dynamic offset between Center of Gravity and Geometric Center. Issue 1 (2022) - Sharma, Manmohan; Kar, Indrani
Abstract: The paper proposes a trajectory tracking control law for a quadrotor with its center of gravity not coincident with the geometric center. A robust adaptive estimation law has been proposed to estimate the center of gravity in presence of disturbances and model uncertainty. The estimation as well as the control law has been developed on SE(3) which makes the approach coordinate invariant. The complete error dynamics with the adaptive estimator has been proved to be stable mathematically. Simulation results have been proposed to validate the advantages of our approach.